Soft Bycatch Reduction Devices for Bottom Trawls : A Review - Boopendranath, M R; Sabu, S; Gibinkumar, T R; Pravin, P (Fishery Technology, 2025)
Trawling, though an efficient and popular method of commercial fishing, is known to be one of the least selective methods of fish capture. FAO Code of Conduct for Responsible Fisheries has stressed the need for development and improvement of fishing technology that eliminates bycatch in order to promote sustainability and conservation of fishery resources. Devices that can be used to reduce bycatch are generally known as Bycatch Reduction Devices (BRDs). BRDs made of soft materials like netting and rope frames with minimum use of rigid parts are called Soft BRDs. Soft BRDs such as square mesh window, rope BRD, radial escapement device, extended funnel BRDs, monofilament BRD, Neil Olsen BRD, trawl flow regulative ecological friendly netting device (TREND), bigeye BRD, V-cut BRD, diamond BRD, Lake-Arthur BRD, Authement-Ledet excluder, separator panel BRD, Morrison soft TED, Parker soft TED, Andrews soft TED and sieve net have been deployed in commercial and experimental fishing operations in different fisheries. In this paper, an attempt is made to review the bycatch issues and BRDs, in general, and soft BRDs, in particular, in the world trawl fisheries.